Lysophosphatidic Acid and Several Neurotransmitters Converge on Rho-Kinase 2 Signaling to Manage Motoneuron Excitability - García-Morales, Victoria; Gento-Caro, Ángela; Portillo, Federico; Montero, Fernando; González-Forero, David; Moreno-López, Bernardo (Frontiers in Molecular Neuroscience, 2021)
Intrinsic membrane excitability (IME) sets up neuronal responsiveness to synaptic drive. Several neurotransmitters and neuromodulators, acting through G-protein-coupled receptors (GPCRs), fine-tune motoneuron (MN) IME by modulating background K+ channels TASK1. However, intracellular partners linking GPCRs to TASK1 modulation are not well-known yet. We hypothesized that isoform 2 of rho-kinase (ROCK2), acting downstream GPCRs, mediates adjustment of MN IME via TASK1. Electrophysiological recordings were obtained from hypoglossal MNs (HMNs) from adult and neonatal rats, neonatal knockout mice for TASK1 (task1-/-) and TASK3 (task3-/-, the another highly expressed TASK subunit in MNs), and primary cultures of embryonic spinal cord MNs (SMNs). The small-interfering RNA (siRNA) technology was also applied to knockdown either ROCK1 or ROCK2. Furthermore, ROCK activity assays reported ability of various physiological GPCR ligands to stimulate ROCK. Microiontophoretically applied H1152, a ROCK inhibitor, and siRNA-induced ROCK2 knockdown both depressed AMPAergic, inspiratory-related discharge activity of adult HMNs in vivo, which mainly express the ROCK2 homolog. In brainstem slices, intracellular constitutively-active ROCK2 (aROCK2) led to H1152-sensitive HMN hyper-excitability. aROCK2 inhibited pH-sensitive TASK1-mediated currents in SMNs. Conclusively, aROCK2 increased IME in task3-/-, but not in task1-/- HMNs. The physiological neuromodulator lysophosphatidic acid (LPA) impacted MN IME via TASK1 by enrolling Gi/o-protein and ROCK2, but not ROCK1. Finally, two neurotransmitters, TRH and 5-HT, which increase MN IME by TASK1 inhibition, stimulated ROCK2 and depressed background conductance via Gq/ROCK2 signalling. Outcomes suggest that LPA and several neurotransmitters manage MN IME via Gi/o/Gq-protein-coupled receptors, downstream ROCK2 activation, and subsequent inhibition of TASK1 channels.